Laboratory Diagnostic Tools for Syphilis: Current Status and Future Prospects - Luo, Yuting; Xie, Yafeng; Xiao, Yongjian (Frontiers in Cellular and Infection Microbiology, 2021)
With the increasing number of patients infected with syphilis in the past twenty years, early diagnosis and early treatment are essential to decline syphilis prevalence. Owing to the its diverse manifestations, which may occur in other infections, the disease often makes clinicians confused. Highly specific and sensitive diagnostic methods are urgently needed. Rabbit infection test, morphological observation, immunohistochemical assay, serologic tests and bacterial composition detection have been applied to diagnose syphilis. Rabbit infection test is considered a sensitive and reliable method for detecting T. pallidum in clinical samples and used as a historical standard for diagnose syphilis. Morphological observation including dark-field microscopy, silver-staining and direct fluorescent antibody staining for T. pallidum can be used as a direct detection method for chancre specimens in primary syphilis. Immunohistochemistry is a highly sensitive and specific assay, especially in the lesion biopsies from secondary syphilis. Serologic tests for syphilis are widely adopted using nontreponemal or treponemal tests by either the traditional or reverse algorithm and remain the gold standard in the diagnosis of syphilis patients. In addition, bacteria composition detection is capable of detecting T. pallidum DNA and spirochete proteins in the samples from patients with syphilis. Notably, PCR is probably a promising method but remains further improvement. These methods mentioned above play an important role in various stages of syphilis. This review provides a summary of the performance characteristics of detection method for syphilis.